The Takeover Deterrent Effect of Open Market Share Repurchases - BILLETT, MATTHEW T.; XUE, HUI (Journal of Finance, 2007)
ABSTRACT This paper examines whether open market share repurchases deter takeovers. We model pre‐repurchase takeover probability as a latent variable and examine its impact on the firm's decision to repurchase shares. Given specification tests reject the Tobit model, we turn to the censored quantile regression method of Powell (1986, Journal of Econometrics 32, 143–155). We find a significantly positive relation between open market share repurchases and takeover probability, and we reconcile empirical findings in previous studies that contradict predictions. Repurchase activity is inversely related to firm size, consistent with smaller firms having greater information asymmetry, and is related to temporary, but not permanent, cash flows.